Entre o comércio e a governação local. Fernão Gonçalves Façanha: um mercador eborense de finais da Idade Média - Joaquim Bastos Serra (Medievalista)
In this paper, we intend to follow the social and political trajectory of the merchant Fernão Gonçalves Façanha who conducted his professional activity in Évora, one of the most important cities of medieval Portugal, in the second half of the 14th century. This is a powerful businessman who held various positions in the municipal administration and in other urban institutions and played a relevant role in the public life of the city. Despite the crisis and the troubles that have marked much of the time in which he lived, Fernão Gonçalves will experience a process of enrichment and social empowerment, which will progressively bring him closer to the leading group. His route is of great historiographical interest, as it constitutes a good example of someone who knew how to take advantage of the opportunities of a context which was largely favorable to mobility and, to start a process of social ascent based on material wealth, but where the relational framework and political options are equally essential.